Berbagi Bahasa dan Harapan: Pengalaman Mengajarkan Bahasa Inggris untuk Anak Pengungsi Imigran di Hotel Kolekta, Batam - Bal Janatte Raj Kaur; Nafa Indah Sasmi; Nurhayati Balqis (Social Engagement: Jurnal Pengabdian Kepada Masyarakat, 2023)
This article discusses the English language teaching program for immigrant refugee children at Hotel Kolekta, Batam. The program aims to provide access to quality English education, help improve the communication skills of immigrant refugee children, and provide hope and encouragement in facing life's challenges. Innovative and engaging English teaching methods were successfully implemented, and the program positively affected the authors. The program provided valuable lessons on the importance of learning from and sharing with others of different cultural and social backgrounds.